PARTISIPASI POLITIK DALAM PILKADA PERSPEKTIF KELAS DAN KEKUASAAN DALAM SOSIALISME MARXIST DI KABUPATEN BUTON SELATAN - Pardana, Deki; Jasiyah, Rabiatul; Suriadi, Suriadi; Rusdin, Rusdin (Jurnal Pengabdian Masyarakat Berkarya, 2024)
The socialization of political participation in the 2024 Simultaneous Regional Elections in South Buton Regency was carried out by the Panwaslu of Batuatas Sub-district with the aim of increasing public awareness of their voting rights and political roles. This socialization uses a Marxist socialism perspective to explain how social class and power influence the political process. The methods used included discussions, seminars and the utilization of social media to reach more layers of society. The results show an increase in political understanding, especially among marginalized groups, as well as increased participation in election monitoring. With more critical political awareness, the community is expected to elect leaders who truly represent the interests of the people and maintain the integrity of local democracy. This activity contributes to efforts to build a more inclusive and equitable political system in South Buton District.